Analysis of Directive Speech Acts in the Anime Film Detective Conan: A Pragmatic Study (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
Language functions not only as a means of communication but also as a reflection of the speaker’s cultural identity. Along with technological developments, communication is also conveyed through visual media such as anime, which presents distinctive linguistic features in its character dialogues. This study aims to describe the types of directive speech acts in the anime film Detective Conan based on linguistic markers and to explain the influence of social relationships between speakers and hearers on their usage. This research applies a pragmatic approach using Namatame’s theory, which classifies directive speech acts into six types: meirei, irai, kinshi, kyoka, kankoku, and kanyuu. The method employed is descriptive qualitative with a note-taking technique. The data were obtained from 15 Detective Conan anime films (1997–2025), yielding 211 data points, from which 6 representative samples were selected based on type representation, contextual clarity, and variation in social relationships. The results show that all types of directive speech acts proposed by Namatame are present in the data, with irai (requests) appearing most frequently (75 data), followed by meirei (commands) (68 data), while kyoka (permission) is the least frequent (6 data). Furthermore, social relationships influence the selection of directive forms; however, situational context also plays a significant role, indicating that both factors are interconnected in pragmatic analysis.
Keywords: directive speech acts; pragmatics; linguistic markers; social relations; anime